2022
DOI: 10.1002/app.53327
|View full text |Cite
|
Sign up to set email alerts
|

Conductive double‐network hydrogel for a highly conductive anti‐fatigue flexible sensor

Abstract: Improving the mechanical properties of hydrogels is a prime example of their large-scale, diverse applications. Herein, we report a one-pot method for preparing a double network system hydrogel where the polyvinyl alcohol served as the first polymer backbone, acrylamide as the second network, and N, N 0 -Methylenebisacrylamide as the cross-linker, and the prepared hydrogels presented excellent mechanical properties with 1168% tensile strain and 598 kPa compressive strength. Through the metal-ligand bonds, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Comprehensive researches showed that a dramatic enhancement in the mechanical strength could be obtained when the ratio of the two networks was within a suitable range 18 . Owing to their extremely high mechanical strength and toughness, double‐network hydrogels have received extensive attention, receiving wide applications in the fields of material chemistry, biomaterials, medical engineering, and energy chemistry 28–33 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive researches showed that a dramatic enhancement in the mechanical strength could be obtained when the ratio of the two networks was within a suitable range 18 . Owing to their extremely high mechanical strength and toughness, double‐network hydrogels have received extensive attention, receiving wide applications in the fields of material chemistry, biomaterials, medical engineering, and energy chemistry 28–33 …”
Section: Introductionmentioning
confidence: 99%
“…18 Owing to their extremely high mechanical strength and toughness, double-network hydrogels have received extensive attention, receiving wide applications in the fields of material chemistry, biomaterials, medical engineering, and energy chemistry. [28][29][30][31][32][33] Stimuli-responsive hydrogels belong to a new type of intelligent materials that are responsive to various external stimuli. Their physical and chemical properties can be tuned by the applied stimuli, providing the opportunity of fabricating tailorable dynamic functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…12,17 The second network of covalent crosslinking ensures that the hydrogel has sufficient strength and toughness, so that the DN hydrogel possesses enhanced fatigue resistance and reusability, which make it suitable for use as a flexible sensing material. [14][15][16][17][18] Carrageenans (CGs) with sulfonic groups are natural polysaccharides derived from red marine algae. They are now available on industrial-scale biopolymers and applied in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical property of the DN hydrogel has been greatly altered, mainly because the first network of noncovalent physical crosslinking is suitable for the “sacrificial bond” during the process of strain in materials; moreover, it effectively dissipates energy and maintains the soft covalent network 12,17 . The second network of covalent crosslinking ensures that the hydrogel has sufficient strength and toughness, so that the DN hydrogel possesses enhanced fatigue resistance and reusability, which make it suitable for use as a flexible sensing material 14–18 …”
Section: Introductionmentioning
confidence: 99%
“…Conductive elastomers are crucial in reducing the gap between intelligent robots and humans, [1][2][3] given the rapid development of intelligent machines enabled by advancements in electronic devices and materials. Furthermore, systems such as flexible sensors, [4][5][6] intelligent robots, [7][8][9] motion-monitoring equipment, [10][11][12] and supercapacitors [13][14][15] have witnessed DOI: 10.1002/smll.202304828 new developments. Conductive elastomers exhibit mechanical properties such as ductility and toughness as well as conductivity.…”
Section: Introductionmentioning
confidence: 99%